Estimated costs of preoperative evaluation of postmenopausal hysterectomy for prolapse at a safety-net hospital: an observational descriptive studyAJOG Global Reports at a Glance - Sam J.F. Melville, BS; Syem Barakzai, MD; Molly Dahl, MD; Emma Koltun-Baker, BS; Enanyeli Rangel, MD; Christina E. Dancz, MD, MPH (Elsevier, 2022)
BACKGROUND: In practice, preoperative evaluation prior to hysterectomy varies. Unnecessary preoperative evaluation may add cost and risk with little benefit to the patient. OBJECTIVE: This study aimed to describe practice patterns and the associated costs related to preoperative evaluations before hysterectomy for prolapse at a safety-net hospital. STUDY DESIGN: This was a retrospective cohort study of postmenopausal women who underwent a hysterectomy for prolapse. Nonfacility-associated cost data were obtained from the Centers for Medicare Services. The biopsy cost was estimated to be $172.55 and $125.23 for ultrasounds. RESULTS: A total of 505 postmenopausal cases were identified. Of those, 155 (31%) underwent a preoperative biopsy, 305 (60%) had an ultrasound, and 124 (25%) had both. Of those, 72.9% had an indication for a biopsy. A total of 64 biopsies and 216 ultrasounds lacked clear indication. Of those, 56 biopsies were performed for bleeding in cases with an endometrial thickness of <4 mm. The total cost of nonvalue-added testing was $42,576. CONCLUSION: Adherence to a strict preoperative algorithm would have saved $38,092 over the study period, although 0.50% of these biopsies would potentially have detected endometrial cancer preoperatively. These results underscore the value of clinical algorithms at teaching institutions.